Effect of hyperbaric oxygen treatment on liver hepatocyte damage in oral candidiasis immunosuppressed rats - Pargaputri, Agni Febrina; Andriani, Dwi; Hartono, Mardiyanto Riski; Widowati, Kharinna (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Liver is an organ that performs a role in metabolism and detoxification of chemical substances. The use of immunosuppressive drugs excessively not only become predisposing factor for oral candidiasis, but also can cause damage and affect liver’s function. Hyperbaric oxygen treatment was known to preserve hepatocytes and prevent liver damage. This study was aimed to investigate the effect of hyperbaric oxygen treatment on liver hepatocyte damage in oral candidiasis immunosuppressed rats.Method: We divided fifteen Wistar rats randomly into three groups: G1 (healthy rats), G2 (immunosuppressed rats with oral candidiasis), and G3 (immunosuppressed rats with oral candidiasis given hyperbaric oxygen). The immunosuppressed condition was made by giving dexamethasone and tetracycline orally for 14 days. Induction of Candida albicans 0.1 cc was conducted on the fourth day. Hyperbaric oxygen treatment was given for five days continuously. The histopathological changes in the liver were measured by counting the amount of normal hepatocytes, pycnotic, karyolysis, karyorrhexis, and score of necrosis area using light microscope with 400x magnification.Result: The amount of pycnotic, karyolysis, and karyorrhexis hepatocytes increased in G2 and decreased significantly in G3, likewise the score of necrosis area. The statistical test using oneway Anova and LSD test showed significant differences (p<0,05) in pycnotic, karyolysis, and karyorrhexis hepatocytes between G1, G2, and G3.Conclusion: The hyperbaric oxygen treatment effect on liver hepatocyte damage in oral candidiasis immunosuppressed rats.